Considerations of Conservative Treatment After a Partial Ulnar Collateral Ligament Injury in Overhead Athletes: A Systematic Review. (July 2019) - Cascia, Nicole; Picha, Kelsey; Hettrich, Carolyn M.; Uhl, Tim L.
Context: Ulnar collateral ligament (UCL) reconstructions continue to increase without consensus on an evidence-based treatment protocol for nonoperative management. Currently, there is no consensus on an effective nonoperative protocol for partial UCL injuries that uses return-to-play (RTP) rates in determining the outcome of conservative treatment. Objective: To systematically review RTP rates after conservative treatment of partial UCL injuries in overhead athletes along with descriptive components of each conservative intervention to identify an effective evidence-based nonoperative rehabilitation protocol. Data Sources: Articles in PubMed, CINAHL, MEDLINE, Academic Search Complete, and SPORTDiscus were identified in October 2018 based on the following terms: overhead athlete, ulnar collateral ligament, nonoperative treatment, and return to play . Study Selection: Seven retrospective, level 4 studies (n = 196) qualified for analysis. Study Design: Systematic review. Level of Evidence: Level 4. Data Extraction: Study design, level of evidence, demographics, sample size, sports involved, level of competition, grade or type of UCL diagnosis, conservative treatment components, and percentage RTP were extracted. Results: Overall, RTP rates after conservative treatment ranged between 42% and 100% (mean, 78% ± 20%). The most frequently reported components of rehabilitation protocols were (1) a period of rest, (2) stretching, (3) strengthening, and (4) a throwing program. Platelet-rich plasma injections were included in 5 (71%) of the 7 protocols with a rehabilitation period. Conclusion: Conservative treatment is a viable option for partial UCL tears in overhead athletes. A successful rehabilitation protocol includes the use of patient-reported outcomes, a sport-specific tailored treatment plan, kinetic chain strengthening, and an interval throwing program. Factors such as age, grading of tear, level of play, sport, and athlete's perceived well-being should all be considered during treatment decisions.